Community experiences at the aftermath of flood disaster based on cultural context - Nurumal, Mohd. Said; Aung, Khin Thandar; Md Yusoff, Nurul Syamimi (Penerbit Akademia Baru, 2017)
Flooding is one of the most common natural disaster in Malaysia especially East Coast region of Malaysia like as Kelantan, Terengganu and Pahang. As a result of the northeast monsoon rains that starts from November until March and where these states are going to get maximum rainfall that will cause flooding. Flood disaster that happened in 2014 was stated the most incredible event that seriously affect the community than the previous years. There is limited information available concerning their experiences after the catastrophe. This study tried to explore the experiences of all family members at a community who have been experienced flood disaster based on cultural context by using qualitative approach. The data has been analyzed using qualitative content analysis by Graneheim and Lundman (2004). The prominent themes of community were rebuilding property, struggle for food aids, social accountability, community accountability, ways of community response to insufficient water supply and coping method to illness. These discovered findings were the experiences of family in a community together understanding the value of cultural context encountered by the key informants’ aftermath of flood disaster. This in-depth understanding about the flood victims from their cultural context will give some valuable inputs to policy and top management in disaster preparedness, response and recovery for future flood disaster.